Relating household entomological measures to individual malaria risk - Max McClure; Emmanuel Arinaitwe; Moses R. Kamya; Philip J. Rosenthal; Joaniter Nankabirwa; Maxwell Kilama; Alex Musiime; Grant Dorsey; Bryan Greenhouse; Isabel Rodriguez-Barraquer (Malaria Journal)
Abstract Background The gold standard measure of malaria exposure is the entomological inoculation rate (EIR), or the number of infectious bites an individual receives over a given period. Nevertheless, it is unclear whether EIR measured in the households of individuals reflects heterogeneity in those individuals’ infection risk. Methods To investigate this relationship, this study used data collected from a cohort of 439 children aged 0.5–5 years in 239 households from 2011–2016 in three Ugandan districts: low-EIR Jinja, intermediate-EIR Kanungu and high-EIR Tororo. Participants underwent passive and quarterly active surveillance for clinical malaria, defined as fever with positive thick blood smear. Monthly vector densities and sporozoite rates in participating households were estimated using CDC light traps. The association between spatiotemporally smoothed household log2-transformed EIR and individual malaria incidence was assessed using Poisson generalized additive mixed effects models. Results Comparison across sites suggested an increasing relationship between average EIR and malaria incidence. Within-site relationships, however, varied by site, with a positive association in Kanungu (incidence rate ratio [IRR] 1.09, 95% credible interval 1.04–1.14) but none in Jinja (1.02, 0.774–1.26) or Tororo (1.02, 0.986–1.06). Conclusions These results show the relationship between measured EIR and malaria incidence may depend on site-specific transmission dynamics and be strongest at intermediate EIR, while underscoring the challenges of using household-level measures of exposure.